Advances in understanding river‐groundwater interactions. (29th September 2017) - Brunner, Philip; Therrien, René; Renard, Philippe; Simmons, Craig T.; Franssen, Harrie‐Jan Hendricks
Abstract: River‐groundwater interactions are at the core of a wide range of major contemporary challenges, including the provision of high‐quality drinking water in sufficient quantities, the loss of biodiversity in river ecosystems, or the management of environmental flow regimes. This paper reviews state of the art approaches in characterizing and modeling river and groundwater interactions. Our review covers a wide range of approaches, including remote sensing to characterize the streambed, emerging methods to measure exchange fluxes between rivers and groundwater, and developments in several disciplines relevant to the river‐groundwater interface. We discuss approaches for automated calibration, and real‐time modeling, which improve the simulation and understanding of river‐groundwater interactions. Although the integration of these various approaches and disciplines is advancing, major research gaps remain to be filled to allow more complete and quantitative integration across disciplines. New possibilities for generating realistic distributions of streambed properties, in combination with more data and novel data types, have great potential to improve our understanding and predictive capabilities for river‐groundwater systems, especially in combination with the integrated simulation of the river and groundwater flow as well as calibration methods. Understanding the implications of different data types and resolution, the development of highly instrumented field sites, ongoing model development, and the ultimate integration of models and data are important future research areas. These developments are required to expand our current understanding to do justice to the complexity of natural systems. Key Points: Recent breakthroughs in fields such as geostatistics, analytical chemistry, remote sensing, or data assimilation are discussed The relevance of these emerging approaches in characterizing streambeds and modeling river‐groundwater interactions is reviewed Integrating approaches across a range of spatial and temporal scales moves our current conceptual models toward the complexity of natural systems